Lamb waves manipulation by piezoelectric metasurface with tunable diffraction orders - Shao, Shixuan; Chen, Jiyue; Xia, Rongyu; Li, Zheng (Frontiers in Physics, 2023)
In this paper, a piezoelectric metasurface is proposed to manipulate anti-symmetric mode Lamb wave by altering the diffraction order. The metasurface attached on a host plate is symmetrically arranged by out-of-plane polarized piezoelectric patches connected with synthetic inductance circuits. Without changing the physical configuration, the transmitted phase of anti-symmetric mode Lamb wave can be shifted arbitrarily in 0~2π range by the metasurface. Furthermore, the relationship between phase gradient and diffraction order is investigated and different orders of diffraction waves can be obtained by adjusting the shunting inductance circuits. The symmetric transmission and asymmetric transmission from a couple of axis symmetric incident waves can be realized by utilizing +1st order and -1st order diffraction. Moreover, omnidirectionally wave reflection and wave trapping in channelized waveguides can also be realized by utilizing the 0th order diffraction. Results indicate that the proposed piezoelectric metasurface has great potentials in manipulating guided wave with large incident angle and isolating wave propagation.